Pembinaan Prestasi Olahraga Bola Voli Klub Spensata SMP Negeri 1 Tayu Kabupaten Pati - Galih Adi Widodo; Nur Fajrie; Sri Surachmi W (Peneliti.net, 2023)
This study aims to determine the process of coaching volleyball at SMP Negeri 1 Tayu, Pati Regency, both in terms of training programs, infrastructure and facilities, coaches and funding. This study uses a qualitative method with the research location of SMP Negeri 1 Tayu and GOR Pondowan, Tayu District, Pati Regency. In collecting data using interviews, observation and documentation of data sources in the form of informants, namely: principals, coaches, physical education teachers and athletes and documents, namely: charters, coaching program books, photos. The results of the research regarding the achievement development process are (1) the formation of a good training program, (2) Although the infrastructure is not supportive, the solution is to hire a Pondowan GOR, (3) Have a certified and well-qualified trainer, (4) Funding from schools and collaboration with other parties..